Usage of Digitised Scientific Resources in Educational Institutions - Todorov, Todor; Vela, Pajtim (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2023)
Over the years studies of scientific publications were on the rise and controlling their content and references was almost impossible. With the provision of platforms like Scopus, Web of Science, and other science databases, this became much easier due to indexation and citation mechanisms incorporated in these databases. In the paper is made an overview of some popular scientific databases. The accessibility of the platforms to people with visual disabilities is investigated. Also, results from scientific research about application of scientific resources and databases in Kosovo’s education institutions are presented.
Keywords: Scientific Resources; Scientific Metrics; Scientific Platforms; Accessibility; Education